Insights into the lithospheric structure and the tectonic setting of the Barents Sea region by isostatic considerations - EBBING J; S. WIENECKE; BRAITENBERG, CARLA (Geophysical Journal International, 2007)
We study the tectonic setting and lithospheric structure of the greater Barents Sea region by investigating its isostatic state and its gravity field. 3-D forward density modelling utilizing available information from seismic data and boreholes shows an apparent shift between the level of observed and modelled gravity anomalies. This difference cannot be solely explained by changes in crustal density. Furthermore, isostatic calculations show that the present crustal thickness of 35-37 km in the Eastern Barents Sea is greater than required to isostatically balance the deep basins of the area (>19 km). To isostatically compensate the missing masses from the thick crust and deep basins and to adequately explain the gravity field, high-density material (3300-3350 kg m-3) in the lithospheric mantle below the Eastern Barents Sea is needed. The distribution of mantle densities shows a regional division between the Western and Eastern Barents and Kara Seas. In addition, a band of high-densities is observed in the lower crust along the transition zone from the Eastern to Western Barents Sea. The distribution of high-density material in the crust and mantle suggests a connection to the Neoproterozoic Timanide orogen and argues against the presence of a Caledonian suture in the Eastern Barents Sea. Furthermore, the results indicate that the basins of the Western Barents Sea are mainly affected by rifting, while the Eastern Barents Sea basins are located on a stable continental platform.